Deep Penetrating Kerosene Exposure in the Hand Mimicking Deep Space Infection - Guss, Michael S.; Ruchelsman, David E.; Leibman, Matthew I. (Journal of Hand and Microsurgery, 2019)
In this case report, we review the clinical course of an adolescent who sustained a low-velocity, low-pressure, penetrating wound to the midpalmar aspect of the hand with a kerosene containing thermometer. The exposure led to a clinical picture of an acute midpalmar abscess within 24 hours. Despite irrigation and debridement of frank purulent material, cultures and pathology remained negative for infection. This case highlights that kerosene exposure, although rare, can mimic an acute infection with intraoperative findings consistent with sterile purulence. Hand surgeons must be aware of the effects of deep soft tissue exposure with hydrocarbons, such as kerosene and petrol, and should have a low threshold to take the patient to the operating room for thorough irrigation and debridement of the offending substance.
Keywords: case report; hand infection; chemical burn; kerosene; sterile purulence